Serous cystadenocarcinoma of the testis: case report of a rare entity - Mohammed El Fadli; Nada Benhima; Ismail Essâdi; Rhizlane Belbaraka (African Journal of Urology, 2022)
Abstract Background Germ cell tumors account for more than 95% of testicular cancers followed by sex-cord stromal tumors. The occurrence of serous cystadenocarcinoma in testicular and paratesticular tissue is very rare with distinct clinical behavior. Case presentation Herein, we report the case of a 39-year-old man who presented with right testicular swelling. Anatomopathological examination of the right orchiectomy revealed a high-grade paratesticular serous cystadenocarcinoma. Long-term follow-up with close monitoring was adopted in the absence of concomitant metastasis. The patient was disease-free at two years post-surgery. Conclusion Owing to its scarcity, there are no standardized guidelines for optimal management of this histological entity. Sharing case reports provide valuable information to support clinical decisions.